Influential Flows of Legal Philosophy to Jurists’ Thoughts - Dewa Gede Atmadja (Fakultas Hukum, Universitas Warmadewa, 2018)
This paper analyzes several flows of legal philosophy that predispose the thinking of jurists/lawyers. The legal flows include law of nature, classical to modern, legal positivism, sociological jurisprudence and flow American legal realism. In detail, it can be concluded that thus far in Indonesia the dominance of the flow of legal positivism is still quite influential on the thinking of the jurists and legal practice. This study was conducted using normative legal research method. Conceptual approach and statute approach to law were used in collecting and analyzing data of this research. In the data analysis results, it was found that there are various flows of law that significantly influence the thinking of jurists and lawyers, namely Sociological Jurisprudence, Realistic Legal Realism, The Critical Jurisprudence. Thoughts of the jurists are still developing, on the one, hand in relation to the National Law Development debates whether our choice is from the political side of law, codification, modification or unification by prioritizing customary law materials or retaining the patterns of Western law, including legal justice concepts and social justice.